Hybrid Encryption using Symmetric Block and Stream Cipher - Magdum, Nandinee (International Journal of Engineering and Management Research, 2023)
Today’s digital world is entirely managed on the internet digitally. So to confirm the Confidentiality, Integrity and Availability of users data in transit and at rest using a hybrid encryption in place of using a particular encryption algorithm. In this paper we are going to propose the hybrid approach which is a combination of multiple symmetric block ciphers and stream ciphers primarily AES-GCM, Chacha20 Poly-1305, Multi Fernet and Fernet to assure more security in an acceptable time period.